Sports talents: a study of personal attributes of the state of Paraná track and field athletes - Lenamar Fiorese Vieira; José Luiz Lopes Vieira (Revista da Educação Física)
The aim of this study is to investigate which personal attributes are necessary for track and field athletes to be considered talents. It was based on Bronfenbrenner’s (1995) bioecological paradigm. The data were collected through informer’s dossiers, semi-structured interviews, research records and other documents. The subject sample was composed by fourteen talents, thirteen family members, seven coaches, three directors of Paraná Sports and one State Secretary of Sports. Content analysis was used to interpret the data. The results demonstrated that personal attributes, body type and interest were prominent in the beginning of track and field practice. On the other hand, search for activities, power of will, need of companionship were the attributes mostly evidenced by the talents in their specialization phase. It may be concluded that talent is a personal competence attained through a special atmosphere favoring sports activities and based on physical and psychological qualities that qualify the athletes for a good performance.